A Sustainable Approach for Removing Organic Pollutants from Food Processing Effluents Using Unmodified Cocopeat as an Adsorbent - Ab Aziz, Nur Adila; Ruslan, Fatin Najihah; Madhoun, Wesam Al (International Journal of Sustainable Construction Engineering and Technology, 2023)
Food production (chips) uses raw materials such as tapioca, cassava, banana, and many more, which contribute to excessive pollutants in the water. Thus, there is a need to treat effluent sufficiently to prevent undesired pollutants from being released into the receiving water bodies, such as rivers and agricultural drainage systems. This study aims to investigate the effectiveness of cocopeat in removing targeted parameters such as suspended solids (SS), chemical oxygen demand (COD), ammoniacal nitrogen (NH3-N), and total phosphorus (TP) from the chips processing effluent. Batch experiments were conducted to determine optimum operating parameters, including the adsorbent dosage, contact time, and shaking speed. This was done to identify the best removal rates of SS, COD, NH3-N and TP from effluent food processing samples taken from two different discharge points based on their usages. The experimental results show that at the optimum conditions of pH 7, cocopeat dosages of 800 mg/L, contact time of 30 minutes, and shaking speeds of 200 rpm, the unmodified cocopeat achieved 17.3% and 19.8% of SS removal, 35.5% and 28.9% of COD removal, 40.7% and 30.5% of NH3-N removal, and 53.5% and 59.2% of TP removal, from Point A and Point B effluent, respectively. Besides, the maximum adsorption capacity achieved by unmodified cocopeat towards SS (1.5-14.0 mg/g), COD (16.88-17.75 mg/g), NH3-N (0.31-0.32 mg/g) and TP (1.46-1.50 mg/g) are comparable to the adsorption capacities reported by previous researchers. This finding suggests that cocopeat could potentially replace the commercially developed adsorbents for the treatment. Furthermore, this study gave insights into the feasibility of sustainable treatment using cocopeat as an adsorbent for medium-strength effluent. However, it is suggested that further alteration of the cocopeat characteristics, either by chemical or physical modifications, and its sludge disposal method could be explored further to enhance the treatment performance.